Inland adult and child interest in the ocean. Issue 4 (2nd October 2021) - Schuman, Carrie; Stofer, Kathryn; Anthony, Lisa; Neff, Hannah; Soni, Nikita; Darrow, Alice; Chang, Peter
ABSTRACT: Interest is an important precursor to engaging the public in environmental and science learning. We used focus groups to explore ocean learning interests of inland residents of a coastal U.S. state, reasons for those interests, and differences between adults and children. We found adults and children generally had similar interests including categories like physical phenomena, sea life, and human impact on and from the ocean which could be a starting point for designers to gather specific local interests and context. Reasons for interest included knowledge for future decision-making which could be leveraged to encourage behavior change for ocean conservation and stewardship.